2022
DOI: 10.3390/ijms23095020
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Gallate Dual-Targeting PTPN6 and PPARγ Shows Anti-Diabetic and Anti-Obese Effects

Abstract: The emergence of the high correlation between type 2 diabetes and obesity with complicated conditions has led to the coinage of the term “diabesity”. AMP-activated protein kinase (AMPK) activators and peroxisome proliferator-activated receptor (PPARγ) antagonists have shown therapeutic activity for diabesity, respectively. Hence, the discovery of compounds that activate AMPK as well as antagonize PPARγ may lead to the discovery of novel therapeutic agents for diabesity. In this study, the knockdown of PTPN6 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Non-receptor-type protein tyrosine phosphatase 6 (PTPN6), expressed mainly in hematopoietic stem cells, regulates receptor tyrosine kinases by binding to target proteins and dephosphorylating tyrosine substrates ( Ahn et al, 2022 ; Luo et al, 2022 ). The m6A methyltransferase METTL14 promotes proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells in steroid-associated femoral head necrosis by upregulating m6A levels of PTPN6 and activating the Wnt signaling pathway ( Cheng C. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Non-receptor-type protein tyrosine phosphatase 6 (PTPN6), expressed mainly in hematopoietic stem cells, regulates receptor tyrosine kinases by binding to target proteins and dephosphorylating tyrosine substrates ( Ahn et al, 2022 ; Luo et al, 2022 ). The m6A methyltransferase METTL14 promotes proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells in steroid-associated femoral head necrosis by upregulating m6A levels of PTPN6 and activating the Wnt signaling pathway ( Cheng C. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al ( 17 ) demonstrated that EG suppresses proliferation and invasion in human breast cancer cells by modulating the PI3K/Akt pathway, and inhibit downstream targets such as NF-κB p-65, Bcl-2/Bax . Ahn et al ( 18 ) proposed that EG targeting PTPN6 and PPARγ exerts an anti-diabetes effect. Crispo et al ( 19 ) suggested that EG protects PC12 cells against oxidative stress induction through the Nrf2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The purification and expression techniques for PTPN6 and PTPN9 have previously been outlined in literature [ 7 , 13 , 15 ]. Escherichia coli Rosetta (DE3) cells were utilized to express recombinant plasmids encoding PTPN6 and PTPN9, supplied by Merck KGaA, Germany.…”
Section: Methodsmentioning
confidence: 99%
“…The cell viability assay was conducted following the full differentiation of C2C12 myoblasts as previously described [ 15 , 16 ]. Upon achieving complete differentiation, cells were subjected to a 16 h starvation period in low-glucose DMEM (11885084, Gibco BRL, Middlesex, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation